2004
DOI: 10.1143/jjap.43.6303
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization Process in Active-State Pitting-Instability of Active-State Pit Formation

Abstract: From the viewpoint of unstable growth of nonequilibrium fluctuations, the self-organization process of the pit in an active state was examined. At less-noble potentials, anodic dissolution of passive metal initially generates a specific pit, called the active-state pit, having a size similar to that of the conventional polishing-state pit formed at more-noble potentials. The inside of the active-state pit has a random irregular surface, sometimes as a result of crystalline micrograins. It was first concluded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Namely, all the conditions discussed above are reversed, so that anionic specific adsorption makes it unstable, forming etch pits, sometimes leading to pitting corrosion. In the case of cationic specific adsorption, weak adsorption will give rise to pitting formation. …”
Section: Theorymentioning
confidence: 99%
“…Namely, all the conditions discussed above are reversed, so that anionic specific adsorption makes it unstable, forming etch pits, sometimes leading to pitting corrosion. In the case of cationic specific adsorption, weak adsorption will give rise to pitting formation. …”
Section: Theorymentioning
confidence: 99%
“…In previous studies, the instability in pitting corrosion was also examined. [51][52][53][54][55][56][57][58] It was then concluded that two different types of pit characteristic of pitting corrosion, i.e., round uniform pit (polishing-state pit) 56) and random irregular pit (active-state pit), 57) appear with their intrinsic fluctuations. Then, it became clear that the instability of nucleation has a 5 m µ quite a different condition from that of the instability of corrosion, i.e., that of the instability of anodic dissolution.…”
Section: Occurrence Of Instabilitymentioning
confidence: 99%
“…Then, it became clear that the instability of nucleation has a 5 m µ quite a different condition from that of the instability of corrosion, i.e., that of the instability of anodic dissolution. 24,51,57,58) As discussed below, the unstable condition essential to nucleation requires the absence of the intense specific adsorption of the anion, 24) whereas in anodic dissolution, the intense specific adsorption of the anion is indispensable. 51) These opposite conditions for cathodic deposition and anodic dissolution are ascribed to the difference in the conditions for the specific adsorption of anions between anodic and cathodic polarizations.…”
Section: Occurrence Of Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…These two types of nucleation come from different nonequilibrium fluctuations. At the early stage of electrodeposition, there are two different kinds of the unstable processes of the fluctuations (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The first unstable process takes place in the electrical double layer.…”
Section: Introductionmentioning
confidence: 99%